Вы находитесь на странице: 1из 26

# INFINITE SERIES

Sequence:
If a set of real numbers u1 ,u 2 , , un occur according to some definite rule, then it is
called a sequence denoted by { Sn }={ u1 ,u 2 , , un } if n is finite

Or { Sn }={u1 ,u 2 , , un , . } if n is infinite.

Series:
n
u1 +u2 + +u n is called a series and is denoted by S n= u k
k=1

Infinite Series:
If the number of terms in the series is infinitely large, then it is called infinite series and is
un=u 1+u 2+ +un +
denoted by and the sum of its first n terms be denoted by

n
S n= u k =u1 +u2 + + un .
k=1

Convergence:

## An infinite series un is said to be convergent if lim S n=k , a definite unique number.

n

1 1
Example: 1+ + + . .
2 4
1
1 1 1
S n=1+ + 2 + ..+ n1 =
2n ( )
1
=2 , finite.
2 2 2 1
1
2 ( )
Therefore given series is convergent.
Divergence:
lim S n tends to either then the infinite series un is said to be divergent.
n

Example: u n=1+2+3+ . .
n ( n+1 )
S n=
2
lim S n=
n

Therefore un is divergent.

Oscillatory Series:
If lim S n tends to more than one limit either finite or infinite, then the infinite series
n

## un is said to be oscillatory series.

Example:1. u n=11+11+ . . :

{
S n= 1, n is odd
0, n is even
Therefore series is oscillatory.

2. u n=1+(3)+(3)2+ ..
1(1)n 3n
S n=
1+3

n {
lim S n= , nis odd
, n is even
Properties of infinite series:
1. The convergence or divergence of an infinite series remains unaltered on
multiplication of each term by c o .
2. The convergence or divergence of an infinite series remains unaltered by addition or
removal of a finite number of its terms.
Positive term series:
An infinite series in which all the terms after some particular term are positive is called a
positive term series.
Geometric Series test:

The series r n=1+r +r 2 +r 3 + + r n +
n=0

a. Converges if |r|<1
b. Diverges if r 1
c. Oscillates finitely if r=1 and oscillates infinitely if r 1
Proof:

Let S n be the partial sum of rn .
n=0

2 n1
S n=1+r + r + +r

## Case 1: |r|<1 i.e. 1<r < 1

1r n
S n=
1r
1
lim S n=
n 1r
Therefore the series is convergent.

n

r n1
S n=
r1
lim S n=
n

## Therefore the series is divergent.

Case 2ii: r=1 , S n=1+1+1+1+ .+1=n
lim S n= . Therefore the series is divergent.
n

## Case 3i: r 1 i.e. Let r=m

n n
1r n 1(1) m
S n= =
1r 1+ m

n {
lim S n= , nis odd
, n is even
Therefore the series is oscillatory.
Case 3ii: r=1
i.e. S n=11+ 11+ .

n {
lim S n= 1, n is odd
0, nis even
Therefore the series is oscillatory.
Note: If a series in which all the terms are positive is convergent, the series remains
convergent even when some or all of its terms are negative.
Integral Test:
A positive term series f ( 1 ) + f ( 2 )+ .+ f ( n ) + . Where f (n) decreases as n

1

## p-series or Harmonic series test:

1 1 1 1
A positive term series u n= n p =1+ 2 p + 3 p + + n p + . is

i) Convergent if p>1
ii) Divergent if p 1
Proof:
1
Let f ( x )= p
x

1 xp +1
f ( x ) dx= x p dx= p+ 1
1 1
[ ] 1
, For p 1

{
,if p+1>0
1
,if p+1< 0
p1

{
,if p<1
1
,if p> 1
p1

## f ( x ) dx= 1x dx=[ logx ] 1 =

When p=1 ,
1 1

1
Thus np converges if p>1 and diverges if p 1 .

Theorem:

n

Proof:

n

S nS n1

lim S n1=k
n

## lim un=lim Sn lim S n1

n n n

k k=0
Note:

Converse need not be always true. i.e. Even if lim un=0 , then un need not be
n
convergent.
1 1 1
Example 1: u n=1+ 2 + 3 + 4 + ... .

1
1 un= lim = 0
n n
u n= n is divergent by integral test. But
lim
n
Hence lim un=0 is a necessary condition but not a sufficient condition for convergence of
n

un .

Example 2

1
Test the series for convergence, nlogn
n=2

1
Solution: Consider nlogn dn= [ log (logn ) ] 2 =
2

Example 2
2

## Test the series for convergence, n en

Solution: Let x 2=t . Then 2 x dx=dt
t

[ ]
t
2
e e 1
xe x
dx=
2
dt = =
2 1 2 e
1 1

Therefore un is convergent.

Comparison test:

## 1. Let u n and v n be two positive term series. If

a. v n is convergent
b. un v n , n

## 2. Let u n and v n be two positive term series. If

c. v n is divergent
d. un v n , n

## That is if a smaller series diverges then larger also diverges.

Example 2

1
Test the series for convergence, logn
n=2

Solution:
1 1
Let un= and v n =
log n n
log n < n
1 1
>
log n n
u n > vn

1
But v n= n is a p-series with p=1 .

Therefore vn is divergent.

## By comparison test un is also divergent.

Example 2
1
Test the series for convergence, 2n +1
Solution:
1 1
Let un= n and v n =
2 +1 2n

2n < 2n + 1
1 1
> n
2 n
2 +1
vn > u n

1 1
But v n = 2n is a geometric series with r= < 1 .
2

Therefore vn is convergent.

Limit test

## Statement: If un and vn be two positive term series such that

un
lim =k ( 0) . Then
n v n
un and vn behave alike.

## If un diverges then vn also diverge.

Examples 3.
1 3 5
Test the series for convergence, + + +.
1.2 .3 2.3 .4 3.4 .5
Solution :
2n1
un=
n(n+1)( n+2)
1 un
Choose vn = 2 then lim =2
n n vn
1
But v n = n2 with p=2>1 .

## Therefore vn is convergent. By limit test un is also convergent.

Examples 4.

Test the series for convergence, ( n 2+1n )
n=1

( n2 +1+n )
un=( n + 1n )
2
Solution:
( n2 +1+n )
n2 +1n2

n2 +1+n
1

n ( 1+n +1 )
2

1
Let v n= n ( p=1 )
un 1
lim =
n vn 2

Examples 5.

## Test the series for convergence, 3 n3 +1n

Solution:
u n = ( n 3 + 1)
1
3
-n
a 3 - b3 = (a - b)(a 2 + ab + b 2 )
a 3 - b3
a-b =
a 2 + ab + b 2
n3 + 1 - n3
u n = ( n 3 + 1)
1
3
-n =
(n + 1)
2 1
3 3
+ (n 3 + 1) 3 n + n 2
1
=
1
1 3 1 3
2
2
n
1+ 3 +
1 + + 1

n n3

1
Let v n = n2 with p=2>1 .

un 1
lim =
n vn 3

Example 6.

## Test the series for convergence, Solve

21 + 31 + 41 +
331 4 31 531
Solution:

1 1
n 1+ -
n +1 -1 n n
un = =
( n + 2 ) - 1 n 3 1 + 2 3 - 1
3

3
n n
1 5
Let v n= 5 with p= > 1 .
n 2 2

un
lim =1
n vn

## But vn is convergent. By limit test un is also convergent.

Example 7
1 1
Test the series for convergence, n3 tan n
1 1
Solution: un= tan
n
3
n
1
tan
n
We know that lim =1
n 1
n
1 un
Let v n= n4 . Then lim
n vn
=1

Example 8

## Test the series for convergence, 1n log ( n+n 1 )

1 1
Solution: un= log 1+
n n ( )
1 1 1 1
[
2 + 3
n n 2n 6 n ]

[ 1
2
1
3 +
2n 6 n ]
1 un 1
Let v n= n2 . Then lim
n
=
vn 2

## But vn is convergent. By limit test un is also convergent.

Exercises
Test for convergence of the series

2 n3 +1
1. 4 n5 +1
n=0

2 2 2
2 3 4
2. 1+ + + +
2 ! 3! 4 !

1 3 5
3. + + + ..
1.2 .3 2.3 .4 3.4 .5

4.
3n1
2n +1
n
n
5. ( n+1 )n +1

1 1+2 1+2+3
6. 2
+ 2 2 + 2 2 2 +
1 1 +2 1 +2 +3
INFINITE SERIES

DAlemberts Ratio Test: If un is a series of positive terms, and l(a finite value)

then the series is convergent if l<1 , is divergent if l>1 and the test fails if l=1 .

If the test fails, one should apply comparison test or the Raabes test, as given below:

## Raabes Test: If un is a series of positive terms, and

un
lim n
n ( un+ 1 )
1 =l ( finite ) , then the series is convergent if l>1 , is divergent if l<1

## and the test fails if l=1 .

1
Remark: Ratio test can be applied when (i) v n does not have the form p
n

## (iii) nth term has n ! , ( n+1 ) ! ,(n !)2 ect.

(iv) the number of factors in numerator and denominator increase steadily, ex: (

1 1.2 1.2 .3
+ + +
3 3.5 3.5 .7

## Example : Test for convergence the series

2 2 2
2 3 4
1 + 2! + 3! + 4! + .

2 2 2 3
1 2 3 4
>> The given series is of the form 1! + 2 ! + 3! + 4! + whose nth term is un =

2 2
n (n+1)
n! . Therefore un+1 = n+1 !

u n+1 (n+1)
2
n! (n+1)2 n! n+1
un = n+1 ! n2 = n2 . (n+1)( n!) = n2
u n+1
Therefore
lim
n un =
lim
n
( n+1n )
2
=
lim
n
( 1n + n1 )
2
=0 <1

## Example : Discuss the nature of the series

2 3
x x x
1.2 + 2.3 + 3.4 + .

xn
>> un = n(n+1)

n+1 n+1
x x
Therefore un+1 = (n+1)( n+1+1) = (n+1)( n+2)

## u n+1 x n+1 n(n+1) n

Now un = (n+1)( n+2) . x n
= n+2 x

u n+1 n 1
lim lim lim
Therefore n un = n n+2 x = n (1+2/n) x = x
convergent if x < 1
divergent if x > 1

{

## And the test fails if x = 1

1n 1 1
But when x = 1, un = n(n+1) = n(n+1) = n +n
2

## un is of order 1/n2 (p = 2 > 1) and hence un is convergent (when x = 1). Hence we

conclude that un is convergent x 1 and divergent if x > 1

2 3
x x x
Example : Find the nature of series 1 + 2 + 5 + 10 + .

>> Omitting the first term, the given series can be written in the form
1 2 3 n
x x x x
2 2 2 2
1 +1 + 2 +1 + 3 +1 + so that un = n +1

n+1 2 2 2
x n +1 n ( 1+1/ n )
lim
Therefore un+1 =
2
n +2 n+2 . 2
n +2 n+2 x = n n ( 1+2/ n+2/ n 2 ) .x
2

u n+1
lim
That is, n un =x
convergent if x < 1
divergent if x > 1

{

## and the test fails if x = 1.

n
1 1 1
2
But when x = 1, un = n +1 = n2 +1 is of order n2 (p = 2 > 1)

## Therefore un is convergent if x 1 and divergent if x > 1.

2 4
1 x x
Example: Find the nature of the series 2 1 + 3 2 + 4 3 +

2n
x
>> omitting the first term, the general term of the series is given by un = (n+2 ) n+1

2 2n+2
x (n+ 1) x
Therefore un+1 = (n+1+2) (n+1 )+1 = (n+3 ) n+2

## u n+1 x 2n+2 (n+2 ) n+1

un = (n+3 ) n+2 x2 n

(n+2)(n+1 )
=
n+2
n+3 n+1 2
n+2
x
= (n+3) x2

## u n+1 n (1+2 /n )n(1+1/n)

lim lim
n un = n n(1+3/n) . x2 = x2
convergent if x2 < 1
divergent if x 2 > 1

{
Hence by ratio test un is

## and the fails if x2 = 1.

n
(1) 1
When x2 = 1, un = (n+2 ) n+1 = (n+2 ) n+1

## Example : Discus the convergence of the series

3 5 7
x 3 x 3.5 x
x + 2.3 + 2.4 + 5 + 2.4.6 . 7 + (x > 0)

## >> We shall write the given series in the form

3 5 7
1 x 1.3 x 1.3.5 x
x + 2 . 3 + 2.4 . 5 + 2.4.6 . 7 + .

## Now, omitting the first term we have

2n+1
1 .3. 5...(2n1 ) x
un = 2. 4.6 ...2n . 2 n+1

## 1. 3. 5.. .[ 2(n+1)1] x 2( n+1)+1

un+1 = 2. 4.6. ..2(n+1) . 2( n+1)+1

1.3.5...(2n+1) x
2 n+3

## That is, un+1 = 2.4.6....(2n+1) . 2 n+3

1.3.5...(2n1 )(2n+1) x
2 n+3

## That is, un+1 = 2.4 .6....(2n)(2n+2) . 2 n+3

u n+1 1.3.5...(2n1)(2n+1) x
2 n+3 2. 4.6...2n 2 n+1
Therefore un = 2.4 .6....(2n)(2n+2) . 2 n+3 1.3.5...(2n1) . x
2n+1
u n+1 (2 n+1)(2 n+1) x 2
That is, un = (2n+2 )(2 n+3)

u n+1 n(2+1/n)n(2+1/n )x 2
lim lim
Therefore n un = n n(2+2 /n)n(2+3/n ) = x2

convergent if x 2 < 1
2
divergent if x > 1

{
Hence by ratio test, un is

## u n+1 (2 n+1)(2 n+1)

When x2 = 1, un = (2 n+2)(2 n+3 ) and we shall apply Raabes test.

lim
n n
( un
un+1
1
) =
lim
n n
[ (2 n+2 )( 2 n+3)
(2n+1 )2
1
]
=
lim
n n
[ ( 4 n2 +10 n+6 )( 4 n2 +4 n+ 1)
( 2 n+1 )2 ]
2
6 n+5
=
lim
n n
( (2 n+1)2 ) =
lim
n
n (6+5/n )
n2 (2+1/n )2
6 3
4 = 2 >1

## Example : Examine the convergence of

2 6 14 2 n+1 2
1+ 5 x+ 9 x2 + 17 x3 + + 2n+1 +1 xn + .

2 n+1 2
n+1
>> un = 2 +1 xn.

2 n+2 2
n+2
Therefore un+1 = 2 +1 xn+1
u n+1 2 2
n+2
2 +1
n+1
1
un n+2
= 2 +1
n+1
xn+1 2 2 . xn

## n+2 n+2 n+1 n+1

u n+1 2 (12/2 ) 2 (1+1/2 )
un n+2 n+2 n+1 n+1
= 2 (1+1/2 ) .x. 2 (12/2 )

n+1 n+1
(11/2 ) (1+1/2 )
n+2 n
= (1+1/2 ) .x . (11/2 )

## u n+1 (10) (1+0 )

lim
Therefore n un = (1+0 ) . x . (10 ) = x.
convergent if x < 1
divergent if x > 1

## Therefore by ratio test un is

{
and the test fails if x = 1.

2 n+1 2
n+1
When x = 1, un = 2 +1

n+1 n
2 (11/2 )
lim lim
Therefore n un = n 2 n+1 (1+1/2 n+1 ) =1

lim
Since n un = 1 0, un is divergent (when x = 1)

## Example : test for convergence of the infinite series

2! 3! 4!
2 3
1+ 2 + 3 + 44 +

>> the first term of the given series can be written as 1!/11 so that we have,

## n! ( n+1)! (n+1)( n!) n!

n+1 n+1 n
un = nn and un+1 = (n+1) = (n+1) = (n+1)

n n
u n+1 n! n
n n n
n n
Therefore un = (n+1) . n! = (n+1) = n (1+1/n )n
n
u n+1 1 1
lim lim
n un = n (1+1/n)n = e <1

## Cauchys Root Test: If un is a series of positive terms, and

u
1
n
( n) =l (finite) ,
lim
n

then, the series converges if l<1 , diverges if l>1 and fails if l=1.

Remark: Root test is useful when the terms of the series are of the form un=[f ( n ) ] g(n) .

1
We can note : (i) lim n n =1
n

1 1
(ii) lim (1+ ) n =e
n n

x 1
(iii) ) lim (1+ ) n =e x
n n

n3 /2

[ ]

1
1+
n
Example : Test for convergence n=1

n3 / 2

>> un =
[ ]
1+
1
n
1/ n

{[ ] }
n 3/2
1
1+
Therefore (un)1/n =
n
n1 /2
1 n
=
[ ]
1+
1
n =
[ ]
1+
n
n
1
lim
n (un) 1/n =
lim
n
[ ]
1+
n

1
1 n
=
lim
n
( 1+
n ) 1
= e < 1.

Therefore as n , n also

## Therefore by Cauchys root test, un is convergent.

n2
3
Example : Test for convergence

n=1
( 1
n )
n2
3
>> un =
( )
1
n

1/n

[( ) ]
n2
3 3
n

Therefore (un)1/n =
1
n =
( )
1
n

n
lim
n (un)1/n =
lim
n
( 1+
3
4 ) = e-3.

n
x
Therefore n
lim ( ) 1+
n = ex

1
lim 3
That is, n (un)1/n = e < 1, therefore e = 2.7

n 3 /2

## Example : Find the nature of the series

n=1
[ ]
1+
1
n
n3 / 2

>> un =
[ ]
1+
1
n
1/ n

{[ ] }
n 3/2
1
1+
Therefore (un)1/n =
n
n1 /2
1 n
=
[ ]
1+
1
n =
[ ] 1+
n
n
1
lim
n (un)1/n =
lim
n
[ ]
1+
n
1
1 n
=
lim
n
( 1+
n ) 1
= e < 1, since as n , n also

## Therefore by Cauchys root rest, un is convergent.

n2
3
Example : Test for convergence

n=1
( 1
n )
n2
3
>> un =
( )
1
n

1/n

[( ) ]
n2
3 3
n

Therefore (un)1/n =
1
n =
( )
1
n

n n
x
lim
n (un)1/n =
lim
n
( 1+
3
n ) = e-3, since
lim
n
( )
1+
n = ex

1
lim 3
That is, n (un)1/n = e < 1, since e = 2.7.

## Hence by Cauchys root test, un is convergent.

ALTERNATING SERIES
A series in which the terms are alternatively positive or negative is called an alternating
series.

u1 - u2 + u3 - u4 + ... = ( -1)
n -1
un
i.e., n =1

LEBINITZS SERIES

u1 - u2 + u3 - u4 + ... = ( -1)
n -1
un
An alternating series n =1 converges if
(i) each term is numerically less than its preceding term
lim un = 0
(ii) n

lim un 0
Note: If n then the given series is oscillatory.
1 1 1 1
Q Test the convergence of 6 - 13 + 20 - 27 +

1
Solution: Here un = 7 n1

1 1
then un+1 = 7 (n=1)1 = 7 n+6

1 1
therefore, un un+1 = 7 n1 - 7 n+6

(7 n+6 )(7 n1 ) 7
= (7 n1 )(7 n+6 ) = (7 n1)(7 n+6) > 0

## That is, un un+1 > 0, un > un+1

1 1 1
lim lim lim
Also, n un = n 7 n1 = n n (71 /n) =0

## (1 log21 ) (1log31 ) (1log1 4 ) (1log51 )

- + - +
1 1
Solution: Here un = 1 - log(n+1 ) then un+1 = 1 - log(n+2)

1 1
Therefore, un un+1 = log(n+2) - log(n+1 )

log(n+1 )log(n+2)
= log(n+2)log(n+1 ) < 0.

Since (n + 1) < (n + 2)

## un - un+1 < 0 un < un+1

further
lim
n un =
lim
n 1-
[ 1
log(n+1 ) ] = 1 0 = 1 0.

Both the conditions of the Leibnitz test are not satisfied. So, we conclude that the series
oscillates between - and + .

Problems:

## Test the convergence of the following series

1 1 1
( i) 1- + - + ....
2 3 4
1 1 1 1
( ii ) - + - + ....
log 2 log 3 log 4 log 5
( -1)
n -1

n
(iii )
n =1 n +1
( -1) x n
n -1

( iv ) for 0 < x < 1
n = 2 n ( n - 1)

1
( v)
1 + n2

## ABSOLUTELY & CONDITIONALLY CONVERGENT SERIES

an = ( -1)
n -1
un
An alternating series n =1 n =1 is said to be absolutely convergent if the positive

a1 + a2 + a3 + a4 + ... = an
series is convergent.

a = ( -1)
n -1
n un
An alternating series n =1 n =1 is said to be conditionally convergent if
(i) a n
is divergent

a = ( -1)
n -1
n un
(ii) n =1 n =1 is convergent

Theorem: An absolutely convergent series is convergent. The converse need not be true.

an = ( -1)
n -1
un
Proof: Let n =1 n =1 be an absolutely convergent series then a n
is
convergent.

a1 + a2 + a3 + a4 + ... a1 + a2 + a3 + a4 + ...
We know,

a n
By comparison test, n =1 is convergent.

## Q. Show that each of the following series also converges absolutely

a2n an
(i) an2; (ii) 1+ a2n ; (iii) 1+ an

## Solution: (i) Since an converges, we have an 0 as n . Hence for some positive

integer N, |an| < 1 for all n N. This gives a n2 |an| for all n N. As |an| is convergent it
follows an2 converges.
(as an2 is a positive termed series, convergence and absolute convergence are identical).
2
an

2
an

## the convergence of an2 implies the convergence of 1+ a2n .

an |an| |a n|
| |
(iii) 1+an = |1+an| < 1|an| .

As |an| converges, |an| 0 as n . Hence for some positive integer N, we have |an| <
for all n N.
an
| |
This gives 1+an < 2|a | for all n N.
n
an
| |
Now, by comparison test, 1+an converges.
an
That is, 1+ an converges absolutely.
1 1 1 1
3
- 3 ( 1 + 2 ) + 3 ( 1 + 2 + 3) + 3 ( 1 + 2 + 3 + 4 ) + ...
Q. Test the convergence 2 3 4 5

an = ( -1)
( 1 + 2 + ... + n ) = -1 n-1 n = -1 n-1 u
( ) ( ) n
n -1

( n + 1) 2 ( n + 1)
3 2

Solution: Here
1 n2 + n - 1
un - un -1 = >0
2 ( n + 1) 2 ( n + 2 ) 2
then
un +1 < un & lim un = 0
i.e., n

## Thus by Lebinitz rule, a n

is convergent.
1 n 1
an = vn =
Also, 2 n + 1 . Take
2
n

an 1
lim = 0
n v 2
Then n

Since is v n
divergent, therefore a n
is also divergent.
Thus the given series is conditionally convergent.

POWER SERIES
a0 + a1 x + a2 x 2 + ... + an x n + ... - - - - - - - - - - - -(i ) ai
A series of the form where the s are
independent of x, is called a power series in x. Such a series may converge for some or all
values of x.

INTERVAL OF CONVERGENCE
un = an x n
In the power series (i) we have
un +1 a
lim = lim n +1 x
n u n a
Therefore, n n
a 1
lim n +1 = l x<
n a
If n , then by ratio test, the series (i) converges when l and diverges for
other values.
-1 1
<x<
Thus the power series (i) has an interval l l within which it converges and diverges
for values of x outside the interval. Such interval is called the interval of convergence of the
power series.
x2 x3 x 4 x5
x- + - + - ....
Q. Find the interval of convergence of the series 2 3 4 5 .
n +1
xn n x
un = ( -1) un +1 = ( -1)
n -1

## Solution: Here n and n +1

un +1 n
lim = lim x = x
n un n n +1
Therefore,
x <1 x >1
By Ratio test the given series converges for and diverges for .
1 1 1
1 - + - + ...
When x=1 the series reduces to 2 3 4 , which is an alternating series and is
convergent.
1 1 1
-
1 + + + + ...
When x=-1 the series becomes 2 3 4 , which is divergent (by comparison with
p-series when p=1)
Hence the interval of convergence is -1 < x 1 .
n
x
(1)n1
Q. Show that the series 1 2 n+1 is absolutely convergent for | x | < 1,
conditionally convergent for x = 1 and divergent for x = -1.
n
x
Solution. Here un = (-1)n-1 2 n+1
n n+1
(1) x
Therefore un+1 = 2 n+3
n n+1
u (1) x 2n+1
lim | N +1| lim | n1 n
|
n u n = n 2 n+3 (1) x
=
lim
n
|(1)
2n+1
2n+3
x|

=
lim
n
|(1)
n(2+1/n)
n(2+3/n)
x|
=|x|
Therefore by generalized D Alemberts test the series is absolutely convergent if
| x | < 1, not convergent if | x | > 1 and the test fails if | x | = 1.
Now for |x | = 1, x can be +1 or 1.
1 1 1 1
If x = 1 the given series becomes 3 - 5 + 7 - 9 +
1 1
Here un = 2 n+1 , un+1 = 2 n+3
But 2n + 1< 2n + 3 un > un+1
1
lim lim
Also n un = n 2 n+3 =0
Therefore by Leibnitz test the series is convergence when x = 1.
1 1 1 1
But the absolute series 3 + 5 + 7 + whose general term is u n = 2 n+1

1 1
and is of order n = n1/2 and hence un is divergent
Since the alternating series is convergent and the absolute series is divergent when x = 1, the
series is conditionally convergent when x = 1.
1 1 1
If x = -1, the series becomes 3 - 5 - 7 - .
1 1 1
=-
( + + +. . .
3 5 7 ) where the series of positive terms is divergent as shown already.
Therefore the given series is divergent when x = -1.
Thus we have established all the results.
Problems:

( -1) ( -1)
n -1 n -1

n
(i) ( ii )
1. Test the conditional convergence of n =1 n n =2 n +1
sin x sin 2 x sin 3x
3
- 3 + 3 - ....
2. Prove that 1 2 3 is absolutely convergent

## 3. For what values of x the following series are convergent

x2 x3 x 4
( i) x - + - + ....
2 3 4
x 2 x3 x 4
( ii ) x - 2 + 2 - 2 + ....
2 3 4
x x2 x3 x 4
( iii ) - + - + ....
1.2 2.3 3.4 4.5
( iv ) 3x + 34 x 4 + 39 x9 + .... + 3n
2 2
x n + ...

( -1)
n -1

n n
4. Test the nature of convergence

******